Assessment of oropharyngeal swallowing dysfunction in myasthenia gravis patients presenting with difficulty in swallowing. Issue 3 (June 2019) - Kumai, Yoshihiko; Miyamoto, Takumi; Matsubara, Keigo; Samejima, Yasuhiro; Yamashita, Satoshi; Ando, Yukio; Orita, Yorihisa
Abstract: Objective: To examine the correlation between the results of a clinical neurological evaluation and swallowing dysfunction in myasthenia gravis (MG) patients who presented with difficulty in swallowing and underwent videofluorographic (VF) and fiber-optic endoscopic (FE) evaluation. Methods: The swallowing studies of 13MG patients with difficulty in swallowing seen at the Department of Neurology from June 2016 to April 2018 were reviewed. The assessment parameters on VF and FE examination were as follows: swallowing initiation, bolus stasis at the pyriform sinus (PS) and vallecula (VC), and the degree of aspiration. They were assessed using a 4 or 5-point scale. Associations between these parameters and the clinical neurological evaluation, which included the Myasthenia Gravis Foundation of America (MGFA) clinical classification, the MG Activities of Daily Living score, and a quantitative MG score, were statistically determined. Results: No patients demonstrated aspiration. However, in patients MGFA IIb/IIIb disease, the Hydo's FEES scale and pharyngeal residue examined using VF were significantly (p < 0.05) more severe than in patients classified with MGFA IIa/IIIa disease. None of the parameters evaluated with VF and FE correlated significantly with the clinical neurological evaluation except for the grip assessment. Conclusion: While not presenting with aspiration but with swallowing difficulty alone, patients classified with MGFA IIb/IIIb disease, regardless of clinical neurological evaluation, require care addressing the reduced pharyngeal clearance. Controlling the severity of the pharyngeal residue may be the key to preventing silent aspiration, especially in patients with MGFA IIb/IIIb disease.